2021
DOI: 10.1007/s11325-021-02542-6
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the National Health And Nutritional Survey (NHANES) single-item self-reported sleep duration against wrist-worn accelerometer

Abstract: Purpose and methods This study aimed to validate the single-item sleep duration question used in the National Health And Nutritional Survey (NHANES), “How much sleep do you usually get at night on weekdays or workdays (hours)?”, against a wrist-worn accelerometer (ActiGraph GT3X +) in waves 2011–2012 and 2013–2014 among an adult population aged 20 or above (n = 8,438, mean age 49.7, 48% male). Results The accelerometer-measured and self-reported sleep dura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…This study used sleep duration measured by accelerometers, which is an objective method. Whereas self-reported sleep duration is subjective, and previous studies have documented a 0.87 h/day of over-reporting (Lee, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…This study used sleep duration measured by accelerometers, which is an objective method. Whereas self-reported sleep duration is subjective, and previous studies have documented a 0.87 h/day of over-reporting (Lee, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…A recent publication has validated the single-item self-reported sleep duration in NHANES by comparing it with wrist-worn accelerometer data. The study suggested that associations between sleep duration and other health outcomes identified using NHANES data should undergo further examination using more accurate and valid measures of sleep duration ( 16 , 17 ). However, one limitation worth noting is that relying solely on accelerometers does not allow for the differentiation between different sleep stages, such as rapid eye movement (REM) sleep and non-rapid eye movement (NREM) sleep.…”
Section: Methodsmentioning
confidence: 99%
“…The Sleep Disorders Questionnaire was administered to NHANES participants aged ≥16 y, who reported their typical sleep habits on weekdays or workdays for the past month ( 18 ), and we used data from those aged ≥20 y in the present analysis. This Sleep Disorders Questionnaire contains items from two previously validated sleep questionnaires, but it has not been validated in its entirety ( 19 , 20 ). A single question was used to collect sleep duration information: “ How much sleep do you usually get on weekdays or workdays?” Responses to this question were collected in whole numbers between 1 and 11 h, and truncated at ≥12 h. Consistent with previous literature, sleep duration was categorized as “very short” (≤ 4 h), “short” (5–6 h), “adequate” (7–8 h), and “long” (≥9 h) ( 14 ).…”
Section: Methodsmentioning
confidence: 99%